2021
DOI: 10.1016/j.clml.2021.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Multiple Myeloma Biology but not Clinical Outcomes: Results from 3894 Patients in the Myeloma XI Trial

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
18
1
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 21 publications
2
18
1
5
Order By: Relevance
“…In an analysis of 1 960 MM patients enrolled in a phase III clinical trial, sex was associated with overall survival (OS) on univariate analysis (median OS 44·8 months female vs 49·9 months male, P = 0·02) but was not significant in multivariate analysis. Similarly, an analysis of the Myeloma XI trial found no sex differences in progression‐free survival (PFS) or OS 3 …”
Section: Figurementioning
confidence: 99%
See 3 more Smart Citations
“…In an analysis of 1 960 MM patients enrolled in a phase III clinical trial, sex was associated with overall survival (OS) on univariate analysis (median OS 44·8 months female vs 49·9 months male, P = 0·02) but was not significant in multivariate analysis. Similarly, an analysis of the Myeloma XI trial found no sex differences in progression‐free survival (PFS) or OS 3 …”
Section: Figurementioning
confidence: 99%
“…Similarly, an analysis of the Myeloma XI trial found no sex differences in progression-free survival (PFS) or OS. 3 In this report, we describe baseline characteristics and outcomes of patients with MM by sex using two large population-based datasets: the SEER dataset and the Multiple Myeloma Research Foundation (MMRF) CoMMpass dataset with clinical annotation.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Aber aktuelle Forschungsbemühungen zeigten, dass die aufgeführten sozioökonomische Aspekte inkl. Einkommen, Beziehungs- und Sozialstatus sowie Notwendigkeit für sozialmedizinische Unterstützungsangebote systematischer erhoben werden müssen [ 28 , 30 , 31 ]. In eigenen Untersuchungen mit Patient*innen mit multiplem Myelom (MM) hatten 10 % der Studienteilnehmenden ein geringes Einkommen (definiert als < 1025 $/Monat) und 14 % waren ohne Partner*in/allein [ 32 ], was sich in einer prospektiven, randomisierten Sportinterventionsstudie mit Patient*innen mit MM (Manuskript in Vorbereitung) sogar als doppelt so hoch mit 19 % bzw.…”
Section: Ausblick Und Konzept Klassenmedizin Als Lösungsansatzunclassified